2021
DOI: 10.3389/fnsys.2021.655695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anesthesia/Surgery on Gut Microbiota and Fecal Metabolites and Their Relationship With Cognitive Dysfunction

Abstract: Aims: Post-operative cognitive dysfunction (POCD) is the decline in cognitive function of the central nervous system (CNS) after anesthesia/surgery. The present study explored whether anesthesia/surgery altered gut microbiota and fecal metabolites, examining their associations with risk factors of cognitive dysfunction in aged mice.Methods: Sixteen-month-old C57BL/6 mice underwent abdominal surgery under isoflurane anesthesia to establish an animal model of POCD. The Morris water maze test (MWMT) was used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…The increase of Desulfovibrio abundance coincided with abundant microglial accumulation at sites of amyloid deposition in the brain of AD mouse models, which was viewed as an inflammation‐related bacterial profile 30 . R. gnavus was also found to be enriched in post‐operative cognitive dysfunction 31 . These results suggested that the four specific species negatively influenced the cognitive function, and these enrichments accounted for the susceptibility of vulnerable group to NCDs partly.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The increase of Desulfovibrio abundance coincided with abundant microglial accumulation at sites of amyloid deposition in the brain of AD mouse models, which was viewed as an inflammation‐related bacterial profile 30 . R. gnavus was also found to be enriched in post‐operative cognitive dysfunction 31 . These results suggested that the four specific species negatively influenced the cognitive function, and these enrichments accounted for the susceptibility of vulnerable group to NCDs partly.…”
Section: Discussionmentioning
confidence: 81%
“… 30 R. gnavus was also found to be enriched in post‐operative cognitive dysfunction. 31 These results suggested that the four specific species negatively influenced the cognitive function, and these enrichments accounted for the susceptibility of vulnerable group to NCDs partly.…”
Section: Discussionmentioning
confidence: 88%
“…Remarkably, dysregulation of gut microbiota promoted the progression of neurodegenerative diseases and the release of inflammatory markers such as IL-6 and TNF-α ( Yang et al, 2018 ; Dalton et al, 2019 ). In recent years, increasing numbers of animal experiments have confirmed that surgery and anesthesia could induce intestinal microflora imbalance and then affected brain cognitive function through certain mechanisms ( Zhan et al, 2019 ; Lian et al, 2021 ). These pathological mechanisms could be ameliorated by the increase of beneficial bacteria in the gut, such as Bifidobacterium , Lactobacillus , and Galactose oligosaccharide ( Jeong et al, 2015 ; Kobayashi et al, 2017 ; Yang et al, 2018 ).…”
Section: Potential Mechanisms Of Central Neuroinflammation Occurrencementioning
confidence: 99%
“…A novel study suggested that oxidative stress and mitochondrial damage in microglia driven by the gut microbiota are probably the results of the metabolite N6-carboxymethyllysine [ 123 ]. Furthermore, alterations in certain bacteria associated with differential fecal metabolism of tryptophan, kynurenic acid, GABA, 2-indolecarboxylic acid, and glutamic acid in POCD mice suggest that the gut microbiota might contribute to cognitive dysfunction after surgery through neurotransmitter metabolism [ 124 ]. Taking the above findings together, we hypothesized that gut microbiota dysregulation may promote POD through inflammation worsened by a broken intestinal barrier, oxidative stress, and neurotransmitter disorders.…”
Section: Pathological Theoriesmentioning
confidence: 99%